2009
DOI: 10.1016/j.marpetgeo.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating fault seal using a hydrocarbon migration model of the Oseberg Syd area, Viking Graben

Abstract: Publication informationMarine and Petroleum Geology, 26 (6): 764-774 Publisher ElsevierLink to online version http://dx.doi.org/10.1016/j.marpetgeo.2008.05.004Item record/more information http://hdl.handle.net/10197/3028 Publisher's statement þÿ T h i s i s t h e a u t h o r s v e r s i o n o f a w o r k t h a t w a s a c c e p t e d f o r p u b l i c a t i o n i n M a r i n e a n dPetroleum Geology. Changes resulting from the publishing process, such as peer review,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Jev et al 1993;Fristad et al 1997;Ottesen Ellevset et al 1998). Childs et al (2009a) for example, calibrated a critical Pc T ⁄ SGR sealing envelope against known column heights in the Oseberg Syd area of the North Sea by randomly selecting possible fault seal envelopes and identifying those that provided the closest match to the observed column heights of several hydrocarbon accumulations when predicted using a raytracing migration modelling tool (Sylta 1991;Krokstad & Sylta 1996;Childs et al 2002b). A summary of the modelling is given in Fig.…”
Section: Membrane Seals In Explorationmentioning
confidence: 99%
“…Jev et al 1993;Fristad et al 1997;Ottesen Ellevset et al 1998). Childs et al (2009a) for example, calibrated a critical Pc T ⁄ SGR sealing envelope against known column heights in the Oseberg Syd area of the North Sea by randomly selecting possible fault seal envelopes and identifying those that provided the closest match to the observed column heights of several hydrocarbon accumulations when predicted using a raytracing migration modelling tool (Sylta 1991;Krokstad & Sylta 1996;Childs et al 2002b). A summary of the modelling is given in Fig.…”
Section: Membrane Seals In Explorationmentioning
confidence: 99%
“…Manzocchi et al (2010) also review comparisons between empirical and deterministic approaches, and reiterate the point that most of the sensitivity between seal capacity and SGR occurs in the critical SGR range between 0.2 and 0.4 (20-40%). Childs et al (2009) calibrated a regional North Sea migration model involving many faults and concluded that there is a sharp increase in seal capacity around SGR = 0.2 and little sensitivity beyond this value. Hence, the range of SGR where fault seal becomes significant is within the central division (PFFR) in the fault-rock classification summarized above.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key elements that control hydrocarbon accumulation and migration is the faulting system (Ben-Awuah et al 2013;Ben-Awuah et al 2014). Lateral migration of hydrocarbons can be impeded by faults by juxtaposing lithologies against reservoir/carrier units or by forming a layer of high capillary threshold pressure fault rock (Childs et al 2009). During faulting, sediments adjacent to the faults are crushed creating a shale gouge (Yielding et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Methods of incorporating fault and seal properties in hydrocarbon migration studies have evolved significantly over time (Perkins 1961;Lindsay et al 1993;Yielding et al 1997;Davies et al 2003;Childs et al 2009) and focused mainly on the shale content in faults separating juxtaposed reservoirs in migration modelling and fault seal studies. However, there are still opposing views on the best methods to use to properly account for the impact of fault properties in hydrocarbon accumulation and migration studies.…”
Section: Introductionmentioning
confidence: 99%